Efficacy of Rotational Grazing on the Control of Rhipicephalus microplus Infesting Calves in Humid Tropical Conditions - Gabriel Cruz-González; Juan Manuel Pinos-Rodríguez; Miguel Ángel Alonso-Díaz; Dora Romero-Salas; Jorge Genaro Vicente-Martínez; Agustín Fernández-Salas; Jesús Jarillo-Rodríguez; Epigmenio Castillo-Gallegos (Journal of Parasitology Research)
Grazing management through pasture rotation has been mentioned as a viable alternative for the control of Rhipicephalus microplus; however, there is limited information on rotational grazing at field level. The objectives of this research were (1) to evaluate the effect of rotational grazing with 30 and 45 days of pasture rest and continuous grazing (without rest) on R. microplus tick loads in Brahman heifers and its most common crosses with Holstein; (2) to know the parasite dynamics of R. microplus under the three grazing systems in the humid tropics of Mexico; and (3) to determine the effect of the treatments on the characteristics of the pastures (availability of forage biomass, plant height, and soil cover). The experiment was carried out for 1 year from April 2022 to March 2023, with three grazing treatments: Treatments 1 and 2 considered rotational grazing with 30 (RT30) and 45 days of rest (RT45), respectively, and Treatment 3 as continuous grazing (CT00). Thirty calves from 8 to 12 months of initial age were distributed in each treatment (n=10). Every 14 days, the number of engorged and semiengorged female ticks in cattle was determined. Concomitantly, the region’s temperature, relative humidity, and rainfall were recorded, as well as the agronomic characteristics of the pasture. Rotational grazing animals with 30 days of rest had the highest number of ticks, while grazing animals with 45 days of rest had the least. Tick load dynamics among groups did not correlate with climatic variables (p>0.05). The height and grass cover presented significant changes due to grazing (p<0.05), which could influence the tick cycle by the exposure of the soil, modifying the microclimatic conditions and consequently harming the survival and development of R. microplus in the evaluated systems. The negative effect of rotational grazing on the nonparasitic phase of R. microplus deserves further studies.